2015
DOI: 10.3347/kjp.2015.53.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Life History and Biological Characteristics of <I>Fasciola gigantica</I> (Digenea: Fasciolidae)

Abstract: This study was conducted to investigate the life history, morphology, and maturation of larval stages and adult worms of Fasciola gigantica in experimental mice. Lymnaea auricularia rubiginosa was used as the intermediate host, and Oryza sativa was used for encystment of the metacercariae, while Mus musculus was used as the definitive host for maturation study. Fresh eggs from the gall bladder of water buffaloes fully developed into embryonated ones and hatched out at days 11-12 after incubation at about 29ºC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…After 42 days, fully-developed cercariae emerged from the snails and were harvested and developed into metacercariae on 5 × 5 cm cellophane sheets. The metacercariae on cellophane sheets were washed several times with phosphate buffered saline (PBS) and were used immediately to infect buffaloes as described previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…After 42 days, fully-developed cercariae emerged from the snails and were harvested and developed into metacercariae on 5 × 5 cm cellophane sheets. The metacercariae on cellophane sheets were washed several times with phosphate buffered saline (PBS) and were used immediately to infect buffaloes as described previously [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…A larger proportion of floating metacercariae cysts have been observed for F. gigantica , implying that water is an important source of infection in addition to encysted metacercariae on vegetation for F. gigantica [5, 14]. Comparative analysis of the maturation and development times of the parasites in the snail host indicates that as a consequence of higher temperatures F. gigantica develops more rapidly than its temperate counterpart F. hepatica [14]. Furthermore, studies of the infectivity of F. gigantica versus F. hepatica have shown that certain ruminant species/breeds display different susceptibilities to the two species.…”
Section: Introductionmentioning
confidence: 99%
“…Pada sporokista, sel germinal memperbanyak diri dan membentuk massa germinal baru. Masa germinal baru tersebut menghasilkan daughter sporocyst atau dapat menjadi redia (Phalee et al, 2015). Redia yang ditemukan berbentuk memanjang, silindris, ujung anterior mengerucut runcing dengan ujung posterior yang tumpul.…”
Section: Pembahasanunclassified
“…Pada trematoda yang memiliki pola perkembangan redia sebanyak dua kali, redia fase pertama sering disebut mother redia dan redia fase kedua disebut daughter redia. Fase mother redia mengandung sel germinal dan calon redia berikutnya, sedangkan daughter redia merupakan redia yang mengandung calon serkaria yang siap dilepaskan (Phalee et al, 2015).…”
Section: Pembahasanunclassified